PEMBELAJARAN FIQIH SEBAGAI MATA KULIAH WAJIB PADA PERGURUAN TINGGI KEAGAMAAN ISLAM - Maimunah Maimunah (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2019)
The existence of FIQH as the main subject at each PTAI both private and public taught to students has a good purpose for scientific understanding of Islamic law. Learning FIQH has a progressive urgency that is taught science to students so that students are able to understand the basic Islamic law relating to human actions that are categorized as adults. Learning in Islamic religious colleges can choose and implement one or several variants of the integration relationship. The learning is based on Permenristedikti 44/2015 related to SNPT / national standard of higher education. Learning also has an interactive specificity, which occurs between students and lecturers. In interaction, of course, focus on students (Student Centered Learning) so that changes occur experienced by students into the cognitive realm, namely the ability to relate to knowledge, thoughts, and then the ability to prioritize feelings or known as affective terms. Fiqh is defined as a knowledge of Islamic law formulated by Islamic jurists (mujtahid) through the process of reasoning on the verses of the Qur'an and the hadith texts relating to human actions that are intelligent and mature. In the context of fiqh discussion here, fiqh in question is one of the Islamic Religious Education (PAI) courses relating to law, rules and procedures of worship to Allah SWT taught in tertiary institutions. In this case, fiqh is also one part of Islamic Religious Education courses that is directed to prepare students to recognize, understand, live and practice Islamic law which then becomes the basis of their way of life through guidance, teaching, exercise of use, practice and habituation